John Rawls: liberalizmas ir tarptautiniai santykiai - Jokubaitis, Alvydas (Politologija, 2000)
John Rawls The Law of Peoples, with "The Idea of Public Reason Revisited". - Cambridge, Massachusetts; London, England: Harvard University Press, 1999. - 199p.